A randomised trial of an internet weight control resource: The UK Weight Control Trial [ISRCTN58621669] - Thomas James D; Greenwood Darren C; Pollard Jennie E; McConnon Aine; Harvey Emma L; Kirk Sara FL; Ransley Joan K (BMC, 2003)
Abstract Background Obesity treatment is notoriously unsuccessful and one of the barriers to successful weight loss reported by patients is a lack of social support. The Internet offers a novel and fast approach to the delivery of health information, enabling 24-hour access to help and advice. However, much of the health information available on the Internet is unregulated or not written by qualified health professionals to provide unbiased information. The proposed study aims to compare a web-based weight loss package with traditional dietary treatment of obesity in participants. The project aims to deliver high quality information to the patient and to evaluate the effectiveness of this information, both in terms of weight loss outcomes and cost-effectiveness. Methods This study is a randomised controlled trial of a weight loss package against usual care provided within General Practice (GP) surgeries in Leeds, UK. Participants will be recruited via posters placed in participating practices. A target recruitment figure of 220 will enable 180 people to be recruited (allowing for 22% dropout). Participants agreeing to take part in the study will be randomly allocated using minimisation to either the intervention group, receiving access to the Internet site, or the usual care group. The primary outcome of the study will be the ability of the package to promote change in BMI over 6 and 12 months compared with traditional treatment. Secondary outcomes will be the ability of the Internet package to promote change in reported lifestyle behaviours. Data will be collected on participant preferences, adherence to treatment, health care use and time off work. Difference in cost between groups in provision of the intervention and the cost of the primary outcome will also be estimated. Conclusion A positive result from this study would enhance the repertoire of treatment approaches available for the management of obesity. A negative result would be used to inform the research agenda and contribute to redefining future strategies for tackling obesity.